The Role of Ward Head Caring Leadership in Enhancing Nurses’ Work Motivation in Hospitals - Retno Utaminingsih; Asnet Leo Bunga (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Nurses' work motivation plays a crucial role in the quality of nursing services. One factor that significantly shapes work motivation is the ward head's leadership style, specifically caring leadership. This study aims to explore and summarize scientific evidence regarding the influence of ward head's caring leadership on nurses' work motivation in inpatient wards. The method used was a systematic literature review by examining 16 research journals obtained from the PubMed, CINAHL (EBSCOHost), Scopus, and Google Scholar databases. The literature search was conducted following the PRISMA protocol. Articles published between 2020 and 2025 were selected based on inclusion criteria, and those that met these criteria were evaluated for quality through critical appraisal. This study shows that caring leadership has a positive impact on nurses' work motivation and well-being, and can reduce burnout. Effective leadership improves nurses' work engagement by increasing motivation, affective commitment, and reducing work stress levels. Furthermore, the implementation of a caring work environment model has been shown to be effective in creating a healthy work atmosphere and reducing burnout in nurses. Caring leadership improves nurses' work motivation, well-being, and engagement, as well as reducing burnout. The implementation of a caring work environment model has been proven to create a healthy work atmosphere and reduce nurses' stress levels.Keywords: Leadership; nurse managers; work motivation; nursing staff; job satisfaction; inpatient care